Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1001/jamanetworkopen.2023.14336
|View full text |Cite
|
Sign up to set email alerts
|

Association of BCG Vaccine Treatment With Death and Dementia in Patients With Non–Muscle-Invasive Bladder Cancer

Abstract: ImportanceThe BCG vaccine—used worldwide to prevent tuberculosis—confers multiple nonspecific beneficial effects, and intravesical BCG vaccine is currently the recommended treatment for non–muscle-invasive bladder cancer (NMIBC). Moreover, BCG vaccine has been hypothesized to reduce the risk of Alzheimer disease and related dementias (ADRD), but previous studies have been limited by sample size, study design, or analyses.ObjectiveTo evaluate whether intravesical BCG vaccine exposure is associated with a decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 57 publications
(95 reference statements)
0
7
0
Order By: Relevance
“…Due to the long-term non-specific immune effects of BCG exposure, a hypothesis that BCG could decrease the prevalence of AD in the elderly population was proposed (Gofrit et al, 2019a), which was investigated subsequently, and several claims were made previously. First, previous studies supported that BCG treatment is associated with a reduced risk of developing AD or other dementias (Gofrit et al, 2019b;Kim et al, 2021;Klinger et al, 2021;Makrakis et al, 2022;Weinberg et al, 2023). Second, old age was usually known as a risk factor for developing AD (Makrakis et al, 2022).…”
Section: Discussionmentioning
confidence: 95%
“…Due to the long-term non-specific immune effects of BCG exposure, a hypothesis that BCG could decrease the prevalence of AD in the elderly population was proposed (Gofrit et al, 2019a), which was investigated subsequently, and several claims were made previously. First, previous studies supported that BCG treatment is associated with a reduced risk of developing AD or other dementias (Gofrit et al, 2019b;Kim et al, 2021;Klinger et al, 2021;Makrakis et al, 2022;Weinberg et al, 2023). Second, old age was usually known as a risk factor for developing AD (Makrakis et al, 2022).…”
Section: Discussionmentioning
confidence: 95%
“…Details of the missing rates for covariates and the method of multiple imputation are shown in Table S1 and Appendix S1. Adjusted absolute risk differences for 5 and 10 years based on the cumulative incidence information were used to summarize the association between PD and all‐cause mortality (Elhence et al, 2023; Wang et al, 2023; Weinberg et al, 2023). Cumulative incidence at 5 and 10 years were calculated based on multivariable adjusted Cox proportional hazards model (Model 3).…”
Section: Methodsmentioning
confidence: 99%
“…1 It is estimated that the number of PwD living alone will reach 1.47 million by 2025 and 1.81 million by 2040. 2 However, to our knowledge, there are no previous studies on the incidence rate (IR) of missing PwD living alone. Thus, the purpose of this study was to clarify the IR of missing PwD living alone.…”
Section: Disclosure Statementmentioning
confidence: 99%
“…Thus far, five retrospective studies examined the effect of intravesical BCG on the odds ratio of dementia in patients with bladder cancer from different ethnologic backgrounds, both in community settings and in tertiary centers (Table 1). [2][3][4][5][6] These studies included 19 983 BCG treated and 27 222 untreated patients. All studies showed significant decrease in the odds ratio of dementia in patients treated with BCG.…”
mentioning
confidence: 99%
See 1 more Smart Citation